Regulation of cel genes of C. cellulolyticum: identification of GlyR2, a transcriptional regulator regulating cel5D gene expression - Fendri, Imen; Abdou, Laetitia; Trotter, Valentine; Dedieu, Luc; Maamar, Hédia; Minton, Nigel P.; Tardif, Chantal (Public Library of Science, 2013)
Transcription and expression regulation of some individual cel genes (cel5A, cel5I, cel5D and cel44O) of Clostridium cellulolyticum were investigated. Unlike the cip-cel operon, these genes are transcribed as monocistronic units of transcription, except cel5D. The location of the transcription initiation sites was determined using RT-PCR and the mRNA 5′-end extremities were detected using primer extension experiments. Similarly to the cip-cel operon, cel5A and cel5I expressions are regulated by a carbon catabolite repression mechanism, whereas cel44O and cel5D expressions do not seem to be submitted to this regulation. The role of the putative transcriptional regulator GlyR2 in the regulation of cel5D expression was investigated. The recombinant protein GlyR2 was produced and was shown to bind in vitro to the cel5D and glyR2 promoter regions, suggesting that besides regulating its own expression, GlyR2 may regulate cel5D expression. To test this hypothesis in vivo, an insertional glyR2 mutant was generated and the effect of this disruption on cel5D expression was evaluated. Levels of cel5D mRNAs in the mutant were 16 fold lower than that of the wild-type strain suggesting that GlyR2 acts as an activator of cel5D expression.